Applying information visualization on rental houses information for non-resident website simulating sphere visualization technique / Bareerah Hamzah - Hamzah, Bareerah (Faculty of Computer and Mathematical Sciences, 2007)
This research project about applying information visualization on rental houses information for non-resident website simulating sphere visualization technique. The objectives of this research are to identify the characteristics of sphere visualization technique, to find out user requirement about NR website and to demonstrate user interface of rental houses information for NR website simulating sphere visualization technique. The researcher was study about information visualization from many resources such as from books, journals, articles and website to get a clear view and to identify the technique that wants to use. From that researcher was made a comparison of major information visualization techniques with sphere visualization technique. After that researcher was identify the criteria of sphere visualization technique. The criteria that identified are control of contents, movement of sphere and diameter of sphere. Beside that, researcher was distributed a set of questionaire to 50 students from Universiti Teknologi MARA (UiTM), Shah Alam. The questionnaire is used to evaluate current NR website that focus on rental houses information page. From that it was found that, almost all of the respondents agreed that current approach of displaying information on NR website is transform to information visualization approach. Lastly, researcher was design a user interface of rental houses information for NR website using sphere visualization technique. Therefore, all the objectives in this research project have been achieved.